How social media marketing influence green purchase intention: based on Theory of Planned Behavior - Rahmadani, Kesha Dewi Nur; Wardana, Candra Kusuma; Husna, Nadiatul (Manajemen dan Bisnis, 2026)
To promote eco-green products, social media information may serve as the center of business development. Consumers buy the product after gaining knowledge developed throughout social media. Social media, cognitive, and marketing factors combine to influence consumer purchase intentions for green products. This study aims to implement marketing in social media, LOHAS, and PCE into TPB, conducting a comprehensive research to understand consumer attitudes towards green products and their purchase intentions. The theory of planned behavior (TPB) explains and predicts human behavior in the context of PCE and LOHAS. Lifestyles of Health and Sustainability (LOHAS) represent a consumer segment focused on health, sustainability, and social responsibility. Perceived consumer effectiveness (PCE) refers to the context of consumer activism and ethical consumption. The questionnaire survey method was employed to gather data on consumers in Indonesia with a sample size of 172 people. Purposive sampling was conducted to obtain insights from participants. Smart PLS 3.0 was used to analyze the data. Social media plays a part in the dissemination of information as a promotion of environmentally friendly products. Social media marketing has the potential to affect consumer attitudes through PCE and LOHAS. PCE and LOHAS contribute significantly to green purchase intentions.